EFEKTIFITAS HARD DAN SOFT OCCLUSAL SPLINT PADA GANGGUAN SENDI TEMPOROMANDIBULA (Kajian klinis pada seri kasus berdasarkan keluhan nyeri sendi temporomandibula) - R.A Donna Pratiwi; Laura Susanti Himawan; Roselani W. Odang; Djaja Soeminta (Faculty of Dentistry, Universitas Indonesia, 2015)
Occlusal splint is commonly used for treatment of the temporomandibular joint disorder (TMD). It can be made of hard and soft material. Hard occlusal splint (HOS) which was known earlier had been recognized more effective than soft occlusal splint (SOS) which recently gained some popularity. This clinical study based on case series was to determined which type of occlusal splint was more effective for TMD. This study involved 20 subjects and they were divided into HOS and SOS group with 10 subjects in each group. HOS was processed with heat curing acrylic and SOS with vacuum former. Before and after 4 weeks of treatment, 5 TMD symptoms (impaired range of movement, impaired TMJ function, muscle pain, TMJ pain and pain on movement of mandible) were measured using Helkimo diagnostic index. The results were analyzed with Kolmogorov-Smirnov Z's test. The findings showed statistically significant improvement in impaired range of movement and muscle pain in favor of HOS group (p<0.05). Although they were not statistically significant, HOS group showed better improvement than SOS group in TMJ pain and pain on movement of the mandible. In TMJ's function, no changes were found in both groups. IN general, HOS was more effective than SOS for treating TMD in relatively short period of time. Despite of the phenomena, the popularity of SOS was not followed with its effectiveness.